The Economic Impact of HRM Practices in Taiwan: The IT Industry - Chin, Chih-Chun (2009)
This research project discusses the economic impact on human resources management or HRM practices in Taiwan within the nation‟s information and technology (IT) sector. The project begins by establishing the framework of the study which identifies Taiwan‟s technology sector as the target and HRM as the performance factor within the industry. The project continues by illustrating a clear precedent for human resource factors having an influence on overall firm performance in most industries and particularly in the technology sector. This link is made because the IT industry relies so heavily on intellectual property and research and development or R&D which drives firm performance. While operational factors such as manufacturing efficiencies are critical, HRM is viewed as one critical field in which a technology firm can achieve a sustainable competitive advantage. It is due to the fact that IT solutions are broadly available to virtually any IT competitor making the market strategy options of these firms largely dependent upon the human performance factors within the firms themselves. A single Taiwan based technology firm receives the brunt of the analysis, HTC, which competes in the mobile device industry and primarily that of the wireless handset market. HTC is viewed as an innovative technology firm because while it takes advantage of manufacturing efficiencies gained in international low cost markets such as China, it also empowers its design engineers and product specialists to take risks. The study concludes by recognizing that HRM provides a solution for Taiwan‟s technology firms to not only survive the current global recession but to also thrive and potentially emerge as more dominant global players as is the case with HTC.